Evaluasi Kinerja Kompor Gasifikasi Forced Draft Berbahan Bakar Cangkang Sawit - Nini Reflinda R; Sri Helianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Oil production in Riau until the year 2011 has reached 35 million tons and production is produced from palm shell of 2.8 million tonnes . Especially in the application of gasification stove for cooking can improve the efficiency of the use of palm shells . This study uses three units of gasification stove with stove dimension 1 ( H1 = 16 cm , D1 = 10cm ) , stove 2 ( H2 = 16 cm , D2 = 12 cm ) , and the stove 3 ( H3 = 20 cm , D3 = 12 cm ) . The fuel used is oil shell with moisture content of 8% , 9 % and 8 % . Method of boiling water test ( WBT ) is used to evaluate the performance of the stove . Additional parameters such as the operating time and temperature flame of the stove as well as evaluate the performance of the stove . The results were obtained an average start-up time of 4.48 minutes and the operation time of the forced draft gasification stoves reached 13.83 minutes . The thermal efficiency of the gasification burner forced draft is approximately 41.49 % to 60.34 % , with the highest efficiency is a stove with a diameter of 12 cm and height 16 cm . Although the resulting fire is still reddish yellow , but the forced draft gasification stoves capable of producing up to 4.42 kWth heat energy with the highest flame temperature reaches 900oC . These results indicate that the operating conditions of forced draft gasification stoves greatly affect the performance of the stove .  Keywords : Shell oil, gasification stove, Thermal Efficiency